Cathepsin L induced PC-12 cell apoptosis via activation of B-Myb and regulation of cell cycle proteins - Shen Xiao; Zhao Yi-fan; Xu Shu-qing; Wang Long; Cao Hui-min; Cao Ying; Zhu Ying; Wang Yan; Liang Zhong-qin (Acta Pharmacologica Sinica; Vol 40, No 11 (November 2019): Acta Pharmacologica Sinica, 2019)
Cathepsin L (CTSL), a cysteine protease, is responsible for the degradation of a variety of proteins. It is known to participate in neuronal apoptosis associated with abnormal cell cycle. However, the mechanisms underlying CTSL-induced cell apoptosis remain largely unclear. We reported here that rotenone caused an activation of CTSL expression in PC-12 cells, while knockdown of CTSL by small interfering RNAs or its inhibitor reduced the rotenone-induced cell cycle arrest and apoptosis. Moreover, elevation of CTSL and increased-apoptosis were accompanied by induction of B-Myb, a crucial cell cycle regulator. We found that B-Myb was increased in rotenone-treated PC-12 cells and knockdown of B-Myb ameliorated rotenone-stimulated cell apoptosis. Further analysis demonstrated that CTSL inﬂuenced the expression of B-Myb as suppression of CTSL activity led to a decreased B-Myb expression, whereas overexpression of CTSL resulted in B-Myb induction. Reduction of B-Myb in CTSL-overexpressing cells revealed that regulation of cell cycle-related proteins, including cyclin A and cyclin B1, through CTSL was mediated by the transcription factor B-Myb. In addition, we demonstrated that the B-Myb target, Bim, and its regulator, Egr-1, which was also associated with CTSL closely, were both involved in rotenone-induced apoptosis in PC-12 cells. Our data not only revealed the role of CTSL in rotenone-induced neuronal apoptosis, but also indicated the involvement of B-Myb in CTSL-related cell cycle regulation.